Epidemiology of fractures in England and Wales. - van Staa, T; Dennison, E; Leufkens, H; Cooper, C (2001)
Records from the General Practice Research Database were used to derive age- and gender-specific fracture incidence rates for England and Wales during the period 1988-1998. In total, 103,052 men and 119,317 women in the sample of 5 million adults sustained a fracture over 10.4 million and 11.2 million person-years (py) of follow-up. Among women, the most frequent fracture sites were the radius/ulna (30.2 cases per 10,000 py) and femur/hip (17.0 per 10,000 py). In men, the most common fracture was that of the carpal bones (26.2 per 10,000 py); the incidence of femur/hip fracture was 5.3 per 10,000 py. Varying patterns of fracture incidence were observed with increasing age; whereas some fractures became more common in later life (vertebral, distal forearm, hip, proximal humerus, rib, clavicle, pelvis), others were more frequent in childhood and young adulthood (tibia, fibula, carpus, foot, ankle). The lifetime risk of any fracture was 53.2% at age 50 years among women, and 20.7% at the same age among men. Whereas fractures of the proximal femur and vertebral body were associated with excess mortality over a 5 year period following fracture diagnosis among both men and women, fractures of the distal forearm were associated with only slight excess mortality in men. This study provides robust estimates of fracture incidence that will assist health-care planning and delivery.